2021
DOI: 10.1002/cav.2022
|View full text |Cite
|
Sign up to set email alerts
|

ASFNet: Adaptive multiscale segmentation fusion network for real‐time semantic segmentation

Abstract: Recently, the development of deep learning has facilitated continuous progress in the field of computer vision. Pixel-level semantic segmentation serves as a fundamental task in computer vision. It achieves significant results by connecting wider and deeper backbone networks and building fine-grained segmentation heads. However, applications such as self-driving cars are more critical to the computational speed of the algorithms. The trade-off between accuracy and real-time performance of existing algorithms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…In previous work [8], we found that the actual generalization ability of the adaptive multiscale segmentation fusion module is relatively poor. In contrast, as a very effective structure, residual connection [9] can help the network to back propagate more efficiently and prevent the gradient divergence.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In previous work [8], we found that the actual generalization ability of the adaptive multiscale segmentation fusion module is relatively poor. In contrast, as a very effective structure, residual connection [9] can help the network to back propagate more efficiently and prevent the gradient divergence.…”
Section: Introductionmentioning
confidence: 91%
“…We use Adam as our optimizer with weight decay 2e −4 . For data preprocessing, we used the same approach as ASFNet [8]. For fair comparison with 6…”
Section: Experiments and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-level fusion network (MLFNet) 23 performs a feature fusion block to combine spatial details and contextual semantics. Unlike these methods that gradually aggregate features of adjacent stages, adaptive multiscale segmentation fusion network (ASFNet) 27 utilizes an adaptive multiscale module to fuse multi-scale segmentation maps, allowing for effective combination of different levels of features and improved performance.…”
Section: Related Workmentioning
confidence: 99%
“…ERFNet [36] innovatively introduced one-dimensional separable residual blocks, replacing each 3×3 convolution with 3×1 and 1×3 convolutions, resulting in a substantial reduction in the number of parameters. ASFNet [37] proposes an adaptive multiscale segmentation fusion network to fuse multiscale contextual to obtain more precise segmentation results. Recent contributions, such as RegSeg [2], have introduced the D-Block, which utilizes two parallel 3×3 convolution layers with different dilation rates to enhance receptive fields.…”
Section: Real-time Semantic Segmentationmentioning
confidence: 99%